Stereotactic radiosurgery for cavernous angioma of the brain - Chuvashova, Olga; Kruchok, Irina (Ukrainian Neurosurgical Journal, 2012)
Introduction. As today a debate is taking place about the risk of hemorrhage after radiation treatment of brain cavernous angioma, the results of stereotactic radiosurgery (SRS) for this pathology are presented here. Methods. SRS with the use of a linear accelerator “Trilogy” and stereotactic system BrainLab were used to treat 28 patients with cavernous angioma of the brain of different localization. The target volume ranged from 0.18 to 11.62 cm3 (mean 2.16 cm3, median 1.18 cm3), the prescribed dose ranged from 12 to 17 Gy (mean 14.5 Gy, median 15 Gy). The SRS target volume, affected by the prescribed dose, was 88-99% (mean 94.5%, median 95%). The maximum dose ranged from 13.8 to 20 Gy (mean 17 Gy, median 17.2 Gy). MRI was applied to 17 patients with intravenous contrasting within a period of 3 to 11 months after treatment. Results. Improvement in the neurological status was reported in 6 (35.3%) patients. MRI positive dynamics were also observed. 3 (17.6%) patients had neurological deterioration after SRS and MRI negative dynamics. 8 (47.1%) patients exhibited a stable MR picture, 6 of them had no changes in neurological status and 2 showed improvement. Conclusions. SRS is an effective method of treating brain cavernomas, which is aimed at reducing the risk of hemorrhage and decreasing the seizure frequency. Optimizing the prescribed dose (12–14 Gy) will help reduce the risk of hemorrhage with large cavernomas. However, for small cavernomas (less than 3 cm3) and a higher dose (15–16 Gy), the risk of complications in the postradiation period is small, but the probability of cavernoma obliteration is higher.